PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA BADAN PENANGGULANGAN BENCANA DAERAH KOTA SUNGAI PENUH: EMILYA GUSMITA, S.Sos., M.Pd - Emilya Gusmita (JURNAL ADMINISTRASI NUSANTARA, 2018)
This study aims to determine the effect of Occupational Safety and Health (K3) on Employee Productivity in the Full River City Disaster Management Agency, to determine the magnitude of the influence of Occupational Safety and Health (K3) on Employee Productivity in the Full River Region Disaster Management Agency. This type of research is quantitative research to see the effect of the independent variable (Independent) with the independent variable (dependent). In this study, researchers want to see the effect of Occupational Safety and Health (K3) on Employee Productivity in the Full River City Regional Disaster Management Agency. The respondents in this study were 96 people. The results of this study are: obtained the value of Ha is accepted at a significant and ? (0.05)> 0.05 (signifikacy) means that there is a significant effect of Occupational Safety and Health (K3) on Employee Productivity at the Full River City Regional Disaster Management Agency. Then the t-count is 9.399> while the t-table is 1.988. So it can be concluded t-count> from t-table or 9.399> 1.988 then the null hypothesis is rejected and the hypothesis is accepted meaning that there is a significant influence on Occupational Safety and Health (K3) on Employee Productivity.